2017
DOI: 10.3340/jkns.2017.0101.005
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Treatment of Hypothalamic Hamartomas

Abstract: Hypothalamic hamartoma (HH) is a benign indolent lesion despite the presentation of refractory epilepsy. Behavioral disturbances and endocrine problems are additional critical symptoms that arise along with HHs. Due to its nature of generating epileptiform discharge and spreading to cortical region, various management strategies have been proposed and combined. Surgical approaches with open craniotomy or endoscopy, stereotactic approaches with radiosurgery and gamma knife surgery or radiofrequency thermos-coag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…This rare non-neoplastic abnormal mixture of neuronal and glial tissue of the inferior hypothalamus has been postulated to be derived from the mammilo-thalami-cingulate tract, from which HH is networking other brain areas associated with GS or the pathway from the HH to the brainstem and cerebellum [1,11,12].…”
Section: Hypothalamic Hamartomasmentioning
confidence: 99%
See 4 more Smart Citations
“…This rare non-neoplastic abnormal mixture of neuronal and glial tissue of the inferior hypothalamus has been postulated to be derived from the mammilo-thalami-cingulate tract, from which HH is networking other brain areas associated with GS or the pathway from the HH to the brainstem and cerebellum [1,11,12].…”
Section: Hypothalamic Hamartomasmentioning
confidence: 99%
“…Using a recent electroencephalography-functional MRI (EEG-fMRI) studies revealed that the ipsilateral hypothalamus is associated with activation of brainstem tegmentum and contralateral cerebellum; in contrast the cunei, bilateral thalami, caudate nuclei, hippoccampi, paracentral gyri and default mode network (precunei and inferior lateral parietal lobes) are deactivated [1,13]. This activated-deactivated networks result in epileptic discharges through the premotor and frontal opercular areas (voluntary system), which are located on the same side of the broader attachment [1,14] of the HH on the hypothalamus, as well as the ipsilateral thalamus is activated, mainly V A nucleus with the cingulate gyri and the limbic circuit is activated too leading to DM activation (dorso medial thalamic nucleus) with the subsequent "on" activity of orbitofrontal cortex, mesial part of the premotor area and parietal lobe [15] (Figure 7).…”
Section: Hypothalamic Hamartomasmentioning
confidence: 99%
See 3 more Smart Citations